Are Digital and Social Media Marketing Matters for Tajikistan’s Youth Travelers? - Jamshed, Namozov; Gayatri, Gita (ASEAN Marketing Journal, 2025)
This research examines the influence of social media and online marketing on the travel behaviours of youth -domestic - tourists in a capital city of Tajikistan, Dushanbe, as the main destination. With the development of new technologies in the modern digital age, digital tools could significantly change the preferences of travellers to choose tourism destinations. In this regard, social media, with its wide audience through Instagram, Facebook, YouTube, and others, became not only an effective tool for tourism marketing but also for affecting tourism decision-making processes. That's why the study examines the impact of tourists’ attitudes towards online tourism information, such as information quality and its user-friendly accessibility, satisfaction, interaction with digital marketing tools, and behavioural intentions, including intention to visit tourism destinations and electronic word of mouth (eWOM). Adopting a quantitative approach, this study is supposed to conduct a detailed online survey of at minimum 102 respondents among two demographic groups named Gen Z and Millennials aged 18 to 40 years. Data from the initially conducted online survey of 30 respondents who had the ability to organize the travel by usage of digital marketing tools. Based on it, the data were analysed for reliability and validity using IBM SPSS 26. Following that, the main data is expected to be analysed through SEM using Smart PLS 4. The results are expected to show that accessible and high-quality online tourism content strongly shapes tourist satisfaction, which in turn mediates behavioural intentions of travellers. This study is expected to add new literature to the limited research on digital tourism behaviour in Central Asia. That's why it provides practical suggestions for the local tourism agency in Tajikistan to enhance digital strategies to attract more tourists to the destinations.